1987
DOI: 10.1002/j.1552-4604.1987.tb03011.x
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine Therapy in Cocaine Withdrawal

Abstract: Twenty-four cocaine addicts who experienced withdrawal symptoms were studied for six weeks in a double-blind design. Half of the group received daily treatment with bromocriptine and the other half with placebo. Significant relief with bromocriptine was seen almost immediately and continued throughout the detoxification period. The authors speculate that the results are consistent with the "dopamine-depletion model" of cocaine withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Weiss et al 1992;King et al 1993King et al , 1994Parsons et al 1995). Third, dopamine agonists have been shown to reverse some of the effects of cocaine withdrawal in animals and humans (e.g., Dackis and Gold 1985;Giannini et al 1987;Tennant and Sagherian 1987;Hollander et al 1990;Markou and Koob 1992;however, see Handelsman et al 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Weiss et al 1992;King et al 1993King et al , 1994Parsons et al 1995). Third, dopamine agonists have been shown to reverse some of the effects of cocaine withdrawal in animals and humans (e.g., Dackis and Gold 1985;Giannini et al 1987;Tennant and Sagherian 1987;Hollander et al 1990;Markou and Koob 1992;however, see Handelsman et al 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Bromocriptine treatment was generally reported to decrease craving and dysphoria during detoxification [45,82,225], but treatment did not decrease cocaine use and was associated with high dropout rates [225]. Additionally, when administered as a pretreatment medication prior to cocaine self-administration, however, bromocriptine increased heart rate without affecting the subjective effects of cocaine (e.g., euphoria), suggesting that it may have limited utility as a cocaine treatment medication [143].…”
Section: Relapse Prevention Medicationsmentioning
confidence: 96%
“…Bromocriptine, a D 2 dopamine receptor agonist, has been assessed as a possible pharmacotherapy for cocaine dependence in several studies [81,82,92,137,143,171,191,225]. Bromocriptine treatment was generally reported to decrease craving and dysphoria during detoxification [45,82,225], but treatment did not decrease cocaine use and was associated with high dropout rates [225].…”
Section: Relapse Prevention Medicationsmentioning
confidence: 98%
“…Bromocriptine pretreatment (1.2 or 2.5 mg) did not alter the subjective effects of intravenous (iv) cocaine (12.5, 25, or 50 mg), but significant increases in heart rate were again observed 36. Early open studies using 1.25–2.5 mg daily yielded conflicting results and suffered from high dropout rates 37,38. In a double blind placebo‐controlled study with cocaine‐dependent individuals, Giannini et al 38 found that compared to placebo, bromocriptine significantly reduced cocaine craving.…”
Section: Pharmacotherapy For Cocaine Abuse/dependence Based On Neurotmentioning
confidence: 99%